Association of C609T-Inborn Polymorphism of NAD(P)H: Quinone Oxidoreductase 1 with the Risk of Bronchopulmonary Dysplasia in Preterm Neonates - Gavrili, Stavroula; Zachaki, Sophia; Daraki, Aggeliki; Polycarpou, Elena; Manola, Kalliopi; Stavropoulou, Chryssa; Sambani, Constantina; Baroutis, George (American Journal of Perinatology, 2016)
Objectives In bronchopulmonary dysplasia (BPD), direct exposure to oxygen therapy can damage the pulmonary epithelium via oxidative stress. The NAD(P)H:quinone oxidoreductase 1 (NQO1) enzyme detoxifies genotoxic products of oxidative stress. The corresponding gene is subject to an inactivating single-nucleotide polymorphism (C609T), which reduces detoxifying ability. The aim of this study was to investigate whether the C609T NQO1 inborn gene polymorphism is associated with an increased risk of BPD.Study Design Peripheral blood samples from 119 premature neonates ≤ 32 weeks of gestational age (42 BPD and 77 non-BPD) were used for DNA extraction. NQO1 genotyping was performed using the polymerase chain reaction-restriction fragment length polymorphism method.Results A significantly higher frequency of the NQO1 polymorphism was observed in BPD neonates compared with neonates without BPD. All neonates with ≤ 1,000 g birth weight who carried the mutant allele in heterozygous or homozygous state developed BPD. None of the BPD nonaffected group neonates with ≤ 1,000 g birth weight carried the NQO1 polymorphism.Conclusion The higher incidence of NQO1 mutants among BPD neonates as well as the presence of the mutant allele in all neonates with ≤ 1,000 g who developed BPD provided the first evidence for a possible pathogenetic role of the C609T polymorphism in BPD susceptibility due to the reduction or loss of NQO1 enzymatic activity.
Keywords: bronchopulmonary dysplasia; NAD(P)H: quinone oxidoreductase 1; single-nucleotide polymorphism; oxidative stress; neonatal chronic lung disease